Peningkatan Pengetahuan Alat Keselamatan Dasar di Atas Kapal Kepada Guru-Guru SMA Muhammadiyah Al-Amin Sorong - Lay Tjarles; Endang Gunaisah; Hendra Poltak; Anjas AS Komboe; Muhfizar Muhfizar (Politeknik Kelautan dan Perikanan Sorong, 2021)
Safety of life at sea is highly prioritized to reduce the impact of losses on humans, ships and their cargo. The purpose of this community service implementation is to provide an overview and information about marine life in the form of rules about basic safety and skills to use basic safety equipment on ships. There were 29 socialization participants who were teachers of the natural tadabbur group of SMA Muhammadiya Al-Amin Sorong. The results of the participant's observations can follow and demonstrate the practice that was done.